Pengaruh Indeks Pembangunan Terbuka dan Tingkat Pengangguran Terbuka Terhadap Indeks Kemiskinan Sumatera Utara 2008-2020 - Dalimunthe, Muhammad Bukhori; Kaban, Novita; Hutagalung, Marsanda; Situmrang, Venus (Journal of Law, Education and Business, 2025)
Economic development in North Sumatra faces a significant challenge due to poverty.This study aims to assess the influence Open Development Index (IPT) and the Open Unemployment Rate (TPT) on the Poverty Index in North Sumatra during the years 2008 to 2020. Employing multiple linear regression analysis, the study incorporates classical assumption tests to affirm the model's reliability. Findings reveal that IPT and TPT collectively exert a notable influence on the Poverty Index, boasting an R Square value of 0.815, which signifies that these two variables can account for 81.5% of the variations in poverty rates. On an individual basis, TPT exhibits a stronger impact than IPT, suggesting that a rise in unemployment directly leads to an increase in the impoverished population. The outcomes of the heteroscedasticity and autocorrelation assessments reveal that the regression model employed does not face significant issues, thus the analysis results can be regarded as reliable. This study concludes that in order to alleviate poverty in North Sumatra, policies must target enhancing investment in the productive sector, ensuring equitable access to education and healthcare, and generating quality employment opportunities. By implementing these strategic initiatives, it is anticipated that poverty in North Sumatra can be markedly diminished and community well-being can sustainably improve.